SIMULASI PEMODELAN PELUANG KEBANGKRUTAN (RUIN PROBABILITY) PERUSAHAAN ASURANSI DENGAN ANALISIS PENDAPATAN PREMI DAN BEBAN KLAIM - Erizal; Septiadi, Mutia Rachmawati (Premium Insurance Business Journal, 2021)
Ruin probability an insurance companies is defined as condition where the ttotal claim expense that has to be paid is greater than the premium income plus the company’s initial capital. The insurance company has the funds to pay claims that derived from accumulated initial reserve and income of insurance from premiums that has payed. If the company’s funds at time t is smaller than 0 then the insurance company will going bankruptcy. Therefor will be analyzed the premium income that must obtained and the value of claim expense that must be certified by the insurance companies. If the premium income that must obtained is greater, so the funds of insurance company will greater too at the time-t to cover the next claim expense. Ruin probability in the insurance company can be predicted from the simulation of ruin probability model with claim expense frequency which happened at the same time between 0 and t is assumed distribution poisson and claim expense size is distribution exponential. This model could be used by insurance company to take decision when determaining premium whether surplus or ruin.